وەسیەت لە شەریعەتى ئیسلام و یاسادا - گەزنەیى, محەمەد ئەحمەد (Sulaimani Journal for Humanities, 2001)
This research deals with the will in both the Islamic charter and the personat status law, and it consists of an introduction, two parts and finale. The introduction: contains definition of the will and its characteristics, properties, prudence, and evidence of it's legality. The first part deals with its conditions and basic elements. About its basic elements, I gave preponderance to that it has one basis which is the acceptance of devisor, because it is a legal action done with personal willing. and it is an acceptance action, but its proving is formal if the devised properties are real estate or transmissible properties with value more than 500 LD. About its conditions the research deals with conditions of restaror, devisee, and devise properties. The second part: deals with rules of devise matrials and advantages, and the mandatory will, the device of a property more than one time, how to excute the will, how to calculate it from one third of the heritage. The finale: about the termenation of the will, as it ends with withdrawal of testator or by the death of the devisee and other conditions.